Prevalence of Shin Splint among Treadmill Users in Gym - Kanwal Fatima, Zainab Rana, Memoona Khalid, Aliha Abid, Maliha Ahmad, Dur E Nayyab Saba, Khizra Afzal, Zainab Arshad, Aqsa Noureen (Pakistan Journal of Medical & Health Sciences, 2023)
Background: shin splints are depicting a condition in which leg torment and distress in distal posteromedial part of leg is brought about by dreary action and it rejects reasons for torment because of stress cracks or because of ischemia. Purpose of study: Study aimed to find the prevalence of shin splints among treadmill users in gym. Materials & Methods: The study was observational cross-sectional survey. Purposive sampling was done. 152 data were collected from different gyms of Lahore, Faisalabad and Sargodha, Pakistan. Both male and females aged 18-25 years with duration of gym from last 6 months at least 3 days a week and currently using gym were included in study while person with any physical and anatomical disability or history of surgery of lower limb and systemic illness. (e.g., deep venous thrombosis) were excluded from study. Data was analyzed using SPSS V 23. Descriptive statistics in form of frequency and percentages was presented. Pie and bar charts were plotted. Data was collected through self-devised questionnaire and Medial Tibial Stress Syndrome Score and Ankle Brachial Index and Shin Palpation Test were applied Results: Mean age of participants was 21 years. Out of 140 participants after systemic disease exclusion 87% participants felt pain in lower leg. While 57.1 (n=80) showed some or moderate arterial diseases when evaluated through Ankle Brachial Index. 17.9% (n=25) showed positive shin palpation indicating shin splints. Shin splints were twice as likely to occur in physically active people who had previously reported a running-related injury. To stop the problem from worsening, it is crucial to determine whether treadmill users have shin splints. This study was carried out in Sargodha, Punjab, to discover shin splints in treadmill users. The purpose of this study was to shed light on the frequency and origin of shin splints among treadmill users. Athletes who experience medial shin pain (MSP) may be unable to run. The incidence especially among treadmill users was not previously investigated. Since there was no literature on the population chosen, this topic was chosen. Conclusion: Use of treadmill is one of causes of shin splint and factors associated were duration of treadmill use and supervised use of treadmill while person with shin splint have pain during walking, sporting and running activities which reduced activities. Keywords: Shin Splints, Medial Tibial Stress Syndrome, Treadmill, Gym.